Biogeographical, environmental and anthropogenic determinants of global patterns in bird taxonomic and trait turnover. Issue 10 (8th September 2017) - Barnagaud, Jean‐Yves; Kissling, W. Daniel; Tsirogiannis, Constantinos; Fisikopoulos, Vissarion; Villéger, Sébastien; Sekercioglu, Cagan H.; Svenning, Jens‐Christian
Abstract: Aim: To assess contemporary and historical determinants of taxonomic and ecological trait turnover in birds worldwide. We tested whether taxonomic and trait turnover (1) are structured by regional bioclimatic conditions, (2) increase in relationship with topographic heterogeneity and environmental turnover and change according to current and historical environmental conditions, and (3) decrease with human impact. Major Taxa: Birds. Location: Global. Methods: We used computationally efficient algorithms to map the taxonomic and trait turnover of 8, 040 terrestrial bird assemblages worldwide, based on a grid with 110 km × 110 km resolution overlaid on the extent‐of‐occurrence maps of 7, 964 bird species, and nine ecological traits reflecting six key aspects of bird ecology (diet, habitat use, thermal preference, migration, dispersal and body size). We used quantile regression and model selection to quantify the influence of biomes, environment (temperature, precipitation, altitudinal range, net primary productivity, Quaternary temperature and precipitation change) and human impact (human influence index) on bird turnover. Results: Bird taxonomic and trait turnover were highest in the north African deserts and boreal biomes. In the tropics, taxonomic turnover tended to be higher, but trait turnover was lower than in other biomes. Taxonomic and trait turnover exhibited markedly different or even opposing relationships with climatic and topographic gradients, but at their upper quantiles both types of turnover decreased with increasing human influence. Main conclusions: The influence of regional, environmental and anthropogenic factors differ between bird taxonomic and trait turnover, consistent with an imprint of niche conservatism, environmental filtering and topographic barriers on bird regional assemblages. Human influence on these patterns is pervasive and demonstrates global biotic homogenization at a macroecological scale.